2008
DOI: 10.1002/pc.20744
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and properties of activated nanosilica/polypropylene composites with coupling agents

Abstract: In this work, nanosilica/polypropylene composites containing 1 wt% of silica nanoparticles were prepared by melt mixing in a Thermo Haake internal mixer. Prior compounding, nanosilica was subjected to surface activation using sodium hydroxide (NaOH) solution. The effectiveness of the activation process was evaluated by measuring the amount of hydroxyl groups (À ÀOH) on the surface of nanosilica via titration method and supported by FTIR analysis. Two coupling agents namely 3-aminopropyl triethoxysilane (APTES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 19 publications
1
44
1
Order By: Relevance
“…Other authors have confirmed this phenomenon in cases where nano-silica and TiO2 was incorporated into multilayer organic coatings [15][16][17][18][19][20][21][22].…”
Section: Matec Web Of Conferencesmentioning
confidence: 74%
“…Other authors have confirmed this phenomenon in cases where nano-silica and TiO2 was incorporated into multilayer organic coatings [15][16][17][18][19][20][21][22].…”
Section: Matec Web Of Conferencesmentioning
confidence: 74%
“…The band at around 1630 cm −1 is the OH bending vibration of the adsorbed H 2 O [29]. The peaks at ∼1100, ∼800, and ∼470 cm −1 are the stretching vibration of Si OH, the asymmetric stretching vibration of Si O Si, and the symmetric stretching and bending vibrations of Si O Si, respectively [26,27,29,38]. The band at around 950 cm −1 is the out-of-plane bending vibration of OH [28].…”
Section: Ft-irmentioning
confidence: 96%
“…The broad absorption peak at ∼3440 cm −1 corresponds to Si OH and the adsorbed H 2 O [28]. The band at around 1630 cm −1 is the OH bending vibration of the adsorbed H 2 O [29]. The peaks at ∼1100, ∼800, and ∼470 cm −1 are the stretching vibration of Si OH, the asymmetric stretching vibration of Si O Si, and the symmetric stretching and bending vibrations of Si O Si, respectively [26,27,29,38].…”
Section: Ft-irmentioning
confidence: 97%
See 1 more Smart Citation
“…NANOSILICA Besides having a low cost (each gram of nanosilica costs 60 paise) budget, high compressive strength (3801 psi), tensile strength (117.7 MPa), high surface area (750 m 2 /gm), ability to prevent silicosis, reducing percentage of CO 2 , nanosilica (particle size = 4-100 nm, colloidal solid percentage = 30%) also helps in checking solid waste pollution when mixed with recycled concrete aggregates [40]- [43]. Stress-strain behavior of nanosilica is presented in Fig.…”
Section: Nanocrystalline Materialsmentioning
confidence: 99%